Digital Knowledge Maps in Education 2013
DOI: 10.1007/978-1-4614-3178-7_2
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Knowledge Integration Maps

Abstract: Digital knowledge maps are rich sources of information to track students' learning. However, making sense of concept maps has been found challenging. Abstract Digital knowledge maps are rich sources of information to track students' learning. However, making sense of concept maps has been found challenging.Using multiple quantitative and qualitative methods in combination allows triangulating of changes in students' understanding. This chapter introduces a novel form of concept map, called knowledge integratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 65 publications
0
15
0
2
Order By: Relevance
“…A recurrent theme in science education is the discussion of how the structure of novices' knowledge differs from experts' knowledge and how to facilitate the transformation of novices' knowledge to a more expert-like knowledge. It has been repeatedly noted that the effectiveness of experts' knowledge is derived from its organized structure, which allows easy, fast and accurate retrieval of knowledge [1,2]. The interest towards the structure of students' knowledge is well documented in many research reports, and thus its importance hardly needs reiteration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recurrent theme in science education is the discussion of how the structure of novices' knowledge differs from experts' knowledge and how to facilitate the transformation of novices' knowledge to a more expert-like knowledge. It has been repeatedly noted that the effectiveness of experts' knowledge is derived from its organized structure, which allows easy, fast and accurate retrieval of knowledge [1,2]. The interest towards the structure of students' knowledge is well documented in many research reports, and thus its importance hardly needs reiteration.…”
Section: Introductionmentioning
confidence: 99%
“…This method, while is well motivated for link-counting based detection of local structures, derives the global hierarchy-based structure from interpretative analysis rather than from purely structural analysis. To remedy the limitations based on local link-counting, some researchers have suggested that in analysing pre-service teacher students' representations of their knowledge in the form of concept maps, researchers should pay proper attention to the interlinked structure as a whole, not only to local link-counting (see [2] and references therein).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Difficulties of using CMs result primarily from years of rote-mode learning practice in school settings [2]; thus, the use of CCM tasks would also foster meaningful learning instead of rote learning and allow differentiating between those two. Less constrained tasks also provide more insight into students' partial knowledge [6].…”
Section: A Cm-based Knowledge Assessment Tasksmentioning
confidence: 99%
“…Those measures that can be calculated with little effort, such as a number of concepts and relationships, provide little insight into student's understanding [6], but those regarding the quality of CM elements ask for natural language processing. There is still no widely accepted method for scoring concept maps despite numerous attempts to create one (see, for example, [4], [7] or [8]).…”
Section: Introductionmentioning
confidence: 99%